Body composition profiling in a Dutch sarcoidosis population - Cremers, Johanna P; Drent, Marjolein; Elfferich, Marjon D; Nelemans, Patty J; Wijnen, Petal A; Witteman, Ben J; Schols, Annemie M (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Muscle atrophy is a common problem in many chronic inflammatory diseases. It may occur as part of a generalized wasting process (cachexia) or be hidden due to preservation of fatmass (sarcopenia, sarcopenic obesity). Objectives: The aim of this study was to assess the prevalence of cachexia and muscle atrophy in sarcoidosis and their association with disease activity and severity. Methods: A cross-sectional study was performed in 423 sarcoidosis patients. Fat-free mass was assessed as an indirect measure of muscle mass by bioelectrical impedance analysis. Patients were stratified based on body mass index (BMI) and fat-free mass index (FFMI).Muscle atrophy was defined as FFMI <15 kg/m2 for women and <17 kg/m2 for men corresponding to <10th percentile of current reference values; cachexia as BMI <20 combined with muscle atrophy.Multivariate linear regression models were used to adjust for potential confounders. Results: Of the patients examined, 58% were categorized as overweight (37%) or obese (21%), whereas 7% were underweight.Muscle atrophy was present in 25% and cachexia in 5%. Patients with muscle atrophy showed significantly worse lung function (DLCO, FEV1, FVC, all p-values <0.01) and impaired exercise capacity (VO2max, p<0.001). The associations were most pronounced in patients with cachexia. Associations remained significant after adjustment for potential confounders. Conclusions: Muscle atrophy was present in 25% of sarcoidosis patients and was associated withmore severe pulmonary disease. Prospective studies with longitudinal design are needed to assess the association between muscle atrophy and disease severity in sarcoidosis.